RESEARCH OF ENERGY AND POWER CHARACTERISTICS OF ELECTROHYDRAULIC PRESS EQUIPMENT FOR LIGHT INDUSTRY - KARMALITA, ANATOLII; SERGEEV, VITALY; PUNDYK, SERHII (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article describes the development of a stand based on the PVG-8-2-O press for studying the energy and power characteristics of electrohydraulic press equipment for light industry, as well as its structural diagram. The experimental stand includes: an electrohydraulic press; a unit with current and voltage sensors; a pressure sensor; a power supply; a galvanic isolation unit; an analog-to-digital converter; a personal computer. This stand allows you to measure in real time the actual values of voltage, current, and power consumed by the press, as well as determine the pressure in the hydraulic system during the performance of technological operations of cutting. To process and record data coming from the ADC on a PC, a block diagram of a virtual device based on the LabView program was created. In light industry, electrohydraulic press equipment is widely used to perform technological operations of cutting, perforation, embossing, and others. Currently, most light industry enterprises use outdated electro-hydraulic press equipment, and the number of modern presses is not enough to meet the needs of light industry. That is why it is necessary to carry out modernization, preserving the existing equipment, and improve it by installing new elements of mechanization and automation, in accordance with modern standards. The modern development of technology and technology requires new approaches to studying the energy and power characteristics of electro-hydraulic press equipment. It is necessary to develop a new concept of experimental complexes using modern information and measuring systems and an effective methodology for conducting research. The use of modern equipment and software will allow us to study the influence of power and energy factors on the operation of electro-hydraulic press equipment of light industry, which in turn will allow us to improve those modes of press operation where excessive consumption of electrical energy and pressure surges in the system occur.
Keywords: electrohydraulic press; power; pressure; cutting